The influence of social media usage motivations on psychological well-being - Liu, Xiawei; Wan Abas, Wan Anita; Wan Mokhtar, Wan Ikhlas (HRMARS, 2024)
Social media platforms have transformed the ways in which people communicate, connect, and consume material. With smartphones, this has grown to encompass prospects from everyday life all over the world. Of these, one of the fastest-growing platforms is Douyin, as known as TikTok, especially for the young audience. The combination of algorithmic personalization and short-form video contents of Douyin makes it indisputably a compelling tool for both entertainment and social interaction. However, the influence of social media platforms like Douyin on psychological well-being (PWB) has become a critical area of concern, increasingly capturing the attention of researchers and professionals in the field of PWB. This becomes particularly relevant in light of the fact that various motivations for usage on the platform may have positive and negative influences on PWB. The theoretical framework of this paper is rooted in the Uses and Gratifications Theory (UGT) to assess how Douyin use affects PWB. The specific psychological well-being differences that arise from diverse motives for usage form the basis of this research study. For this study, Douyin usage motives are the independent variable, while PWB is the dependent variable. It will also provide additional information about how different motives for using Douyin influence the PWB of user.